2019
DOI: 10.1108/jsbed-04-2019-0125
|View full text |Cite
|
Sign up to set email alerts
|

A framework for cooperation behavior of start-ups

Abstract: Purpose Many start-ups are in search of cooperation partners to develop their innovative business models. In response, incumbent firms are introducing increasingly more cooperation systems to engage with start-ups. However, many of these cooperations end in failure. Although qualitative studies on cooperation models have tried to improve the effectiveness of incumbent start-up strategies, only a few have empirically examined start-up cooperation behavior. The paper aims to discuss these issues. Design/method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…A post hoc test was elaborated in the G*Power 3 software with an average effect size (f 2 ) (0.15), error probability (α) of 5%, a sample of 84 respondents and 4 predictors in the dependent variable (ambidextrous innovation), obtaining a satisfactory statistical power (Ringle, Silva & Bido, 2014). The sample size is satisfactorily aligned with related studies that used such a technique (Garidis & Rossmann, 2019;Theiss & Beuren, 2020). Thus, the sample size is adequate for applying PLS-SEM.…”
Section: Data Analysis Techniquesmentioning
confidence: 83%
“…A post hoc test was elaborated in the G*Power 3 software with an average effect size (f 2 ) (0.15), error probability (α) of 5%, a sample of 84 respondents and 4 predictors in the dependent variable (ambidextrous innovation), obtaining a satisfactory statistical power (Ringle, Silva & Bido, 2014). The sample size is satisfactorily aligned with related studies that used such a technique (Garidis & Rossmann, 2019;Theiss & Beuren, 2020). Thus, the sample size is adequate for applying PLS-SEM.…”
Section: Data Analysis Techniquesmentioning
confidence: 83%
“…Yet, the literature suggests that such collaborations may not always be without challenges. For instance, studies have suggested that both incumbents and start-ups might have unique organizational cultures, management systems, and approaches to risk that might not be keen on losing (Garidis & Rossmann, 2019). Also, start-ups typically aim to explore new niches or create new markets, while established firms often focus on exploiting existing markets, as emphasized by Buckley and Prashantham (2016).…”
Section: Collaboration As Meaningful Means Of Ensuring Ce Implementationmentioning
confidence: 99%
“…Third, our study demonstrates that the solutions provided by our start-ups do not demand a cultural shift within incumbents. While existing literature implies that incumbents might encounter difficulties in aligning with new practices (Garidis & Rossmann, 2019), engaging in collaborations with start-ups as depicted in this study enables incumbents to inject new perspectives and innovative thinking into their organizations without necessitating a sweeping cultural transformation. This pragmatic approach to collaboration ensures the attainment of environmental benefits without unnecessary disruptions or extensive organizational upheaval.…”
Section: The Peculiarity Of the Ce Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Исследователи тематики стартапов также обращаются к обсуждению бизнес-моделей. Так, указывается, что цель стартапов -поиск и дальнейшее масштабирование жизнеспособной модели, которая сможет создать ценность для бизнеса и клиентов [Бланк, 2017;EU Startup monitor, 2018], а не реализация уже существующей бизнес-модели [Garidis, Rossmann, 2019]. Среди других, наиболее часто встречающихся характеристик стартапов -уникальность продукта [What is a startup, 2021], функционирование в условиях неопределенности [Рис, 2020], готовность рисковать [Weiblen, Chesbrough, 2015], креативность и способность распознавать возможности рынка [Bikse, Lusena-Ezera, Rivza, 2018].…”
Section: тревелтех-стартапы: определение понятияunclassified